Costos de produccion de frijol; comparacion entre granos y semillas : Apuntes de clase - Gutiérrez Palacios, Uriel (International Center for Tropical Agriculture, 1990)
Some basic concepts to estimate production costs and evaluate the profitability of bean seed production are analyzed, namely total, fixed, variable, av., and marginal costs; direct and indirect costs; profitability estimates, and comparison among yr and production areas. Based on an example of the Loja region, Ecuador, a single methodology is proposed to compare the grain vs. seed production. (CIAT)